(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
The article analyses the application of the mode of magic realism in Lilliam Rivera’s novel Never Look Back (2021), which retells the Greek myth of Orpheus and Euridice. The essay examines how the elements of the myth are transformed through the Caribbean characters in the contemporary setting of the South Bronx. The first part of the article introduces the theoretical framework of the literary mode known as magic realism. The second section analyses the realistic elements of the narrative and highlights the traumatic experience of the Puerto Rican character, a Hurricane María survivor. The third part examines the magical strain of the narrative and establishes a relationship between trauma and magic realism when the protagonist finds relief via the supernatural. The paper argues that the novel provides a graspable representation of a traumatic event by combining ancient myth with magic realism and Caribbean heritage.